PENGARUH ROTASI KAP MANDATORY DAN VOLUNTARY TERHADAP KUALITAS AUDIT DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN NON KEUANGAN YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Suci Amelia Putri; Hardi '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was aimed to examine empirically the effect of several factors to audit quality. These factors are Mandatory Audit Firm Rotation, Voluntary Audit Firm Rotation, To Audit Quality With Institutional Ownership As A Moderating Variable. The population that will be used in this research are company listed in Indonesia Stock Exchange. This study uses sampel of 60 non financial company listed on the Indonesia Stock Exchange in the period 2012-2014. In this study, audit quality is measured by the level of discrecionery accrual that estimated by Kothari model (2005). The Method used was Purposive Sampling due to availability of data. Collecting data was conducted from Indonesia Stock Exchange.The method of data analysis in this study is use multiple liniear regression with SPPS version 20. The results of this study prove that mandatory and voluntary audit firm rotation is not proven to have an impact on audit quality. Institutional ownership not proven to moderate the relationship between mandatory and voluntary Audit Firm Rotation againts Audit Quality, but institutional ownersship proven to have impact on relationship between voluntary audit firmrotation and audit quality. The Amount of Adjusted R is 0.024 gives the sense that the rate is 2.4 % of level audit quality can be explained by independent variables while 97.6% can be explained by the other independent variabels that are not tested in this study.Keywords : Mandatory, Voluntary, Quality, and Institutional